Hubungan Pengetahuan Tentang Sanitasi Makanan dan Minuman Dengan Personal Hygiene Pedagang Pasar Kuliner Kota Padang Panjang Tahun 2025 - Gusneli , Rati; Erian Fatria; Mellia Fransiska; Asrul Fahmi (LPPM Universitas Negeri Jakarta, 2025)
Food sanitation and personal hygiene are essential aspects of food safety. In the Padang Panjang Culinary Market, many vendors are still found to be neglecting personal cleanliness and proper food handling, which can pose health risks to consumers. Adequate knowledge of food sanitation is believed to influence vendors’ personal hygiene behavior. This study aims to determine the relationship between knowledge of food and beverage sanitation and personal hygiene behavior among street food vendors at the Padang Panjang Culinary Market in 2025. This research used an observational analytic design with a cross-sectional approach. The population consisted of all vendors at the Padang Panjang Culinary Market, totaling 80 individuals. A sample of 62 vendors was selected using purposive sampling. Data were collected using questionnaires and analyzed using univariate and bivariate analyses with the chi-square test. The results showed that 54.8% of respondents had good knowledge of food and beverage sanitation, and 58.1% exhibited good personal hygiene. The chi-square test revealed a significant relationship between knowledge of food and beverage sanitation and personal hygiene behavior (p-value = 0.000; OR = 8.143). There is a significant relationship between knowledge of food and beverage sanitation and vendors' personal hygiene behavior. Vendors with poor knowledge are 8 times more likely to exhibit poor personal hygiene behavior compared to those with good knowledge. Continuous education and interventions are necessary to improve knowledge and hygiene practices among market vendors.